Myeloid leukemia factor 1: A “double-edged sword” in health and disease - Li, Zixuan; Yang, Yuanyuan; Wu, Kun; Li, Yuntao; Shi, Mingxia (Frontiers in Oncology, 2023)
At present, the occurrence and development of malignancies are closely related to abnormal cell cycle regulation. Myeloid leukemia factor 1（MLF1） is a small nucleo-cytoplasmic shuttling protein, which is associated with cell cycle exit, apoptosis, and immune functions. Therefore, it is pertinent to explore the role of MLF1 in health and diseases. Studies to date have suggested that MLF1 could act as a double-edged sword, direct or indirect regulating biochemical activities. In hematopoietic cells, it serves as a protective factor for the development of lineages, and in malignancies, it serves as an oncogenesis factor in malignancies. The diversity of its functions depends on the binding partners, including tumor inhibitor, scaffolding molecule, mitochondrial membrane protein and transcription factors. Emerging evidence indicates that MLF1 affects immune responses as well. This paper reviews the structure, biological function and research progress of MLF1 in health and diseases, in order to provide new insights for future research.